A Novel Model for Authority and Access Delegation Utilizing Self-Sovereign Identity and Verifiable Credentials - Spela Cucko; Muhamed Turkanovic (IEEE Access)
Self-Sovereign Identity (SSI) is a decentralized, user-centric approach to Identity Management (IdM), that allows users to gain control over their digital identity and data. It brings many advantages and reduces the shortcomings of traditional, centralized IdM systems. Despite its positive features, SSI focuses predominantly on direct interactions between two independent entities. It enables direct identification, authentication, authorization, and access to resources and services where the identity holders are the authenticated bearers of their credentials. On the other hand, it does not address primarily indirect identity control, such as delegation, which is an essential part of life situations and natural human relationships. Delegation is particularly common in organizational contexts, and usually arises from the need for greater efficiency, relief, or distribution of work, collaboration, and cooperation and the inability to perform work, tasks, responsibilities, and duties for various reasons. However, it is relatively unexplored within the SSI framework, and requires additional research efforts and the development of new approaches. Consequently, our research aimed to reduce the aforementioned gap and address delegation in the SSI ecosystem comprehensively. Thus, we present a novel authority and access delegation model utilizing Verifiable Credentials, that enable delegation support for existing use cases, workflows, and processes of organizations and companies, providing resources and services to end users. The model includes delegation building blocks, data objects and data flow, delegation phases and processes, and technology-independent components. It is validated with a case study in the field of Education.